The Role of Management Information Systems in Human Resource Competency Development - Namira Fitria; Isa Wijayanti; Ade Budi Santoso; Saiful Romadon; Kraugusteeliana Kraugusteeliana (Politeknik Ganesha Medan, 2023)
In the era of globalisation and advances in information technology, companies or organisations are faced with increasingly fierce competition. Human Resources (HR) is one of the key factors that determine the success of a company in achieving its strategic goals. The competence of strong and qualified human resources is an important capital in increasing the competitiveness of the company. This research aims to identify and analyse how Management Information Systems (MIS) can effectively support the development of HR competencies, as well as identify factors that influence the application of MIS in the context of HR development. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results arrive at the expression that management information system plays a very important role in the development of HR competencies in various organisations and companies. It serves as a strategic tool to collect, store, manage and analyse HR-related data. With management information systems, companies can conduct efficient planning related to employee competency development, identify training needs, and monitor and evaluate the impact of competency development programmes.